2019
DOI: 10.1101/831875
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

EXO70A2 is critical for the exocyst complex function in Arabidopsis pollen

Abstract: Pollen development, pollen grain germination and pollen tube elongation are crucial biological processes in angiosperm plants that need precise regulation to deliver sperm cells to fertilize ovules. Pollen grains undergo two major developmental switches: dehydration characterized by metabolic quiescent state, and rehydration upon pollination that leads to extraordinary metabolic and membrane trafficking activity, resulting in germination and rapid tip growth of pollen tubes. To sustain these processes, many pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 72 publications
(111 reference statements)
1
6
1
Order By: Relevance
“…While EXO70B1 and H7 remained the most expressed paralogs in both WT and exo70A1 seedlings, loss of EXO70A1 leads to further increase in relative transcript abundance of H-group paralogs, especially H1and H2, and to a lesser extent also of F1, as well as to a slight drop in relative abundance of E2 ( Figure 3B). Even though the pollen specific isoform EXO70A2 mRNA levels were in our experiments under the detection limit, recent work by Markovic et al, 2020 indicates the importance of a sporophytic EXO70A2 function of in the exo70A1 plants. Interestingly, the increase of H1 and H2 in both biotic stresses and in the absence of A1 implies that H1 and H2 might compensate functionally for loss of basal A1 level during pathogen response.…”
Section: Gene Expression Of Exo70 Paralogscontrasting
confidence: 74%
“…While EXO70B1 and H7 remained the most expressed paralogs in both WT and exo70A1 seedlings, loss of EXO70A1 leads to further increase in relative transcript abundance of H-group paralogs, especially H1and H2, and to a lesser extent also of F1, as well as to a slight drop in relative abundance of E2 ( Figure 3B). Even though the pollen specific isoform EXO70A2 mRNA levels were in our experiments under the detection limit, recent work by Markovic et al, 2020 indicates the importance of a sporophytic EXO70A2 function of in the exo70A1 plants. Interestingly, the increase of H1 and H2 in both biotic stresses and in the absence of A1 implies that H1 and H2 might compensate functionally for loss of basal A1 level during pathogen response.…”
Section: Gene Expression Of Exo70 Paralogscontrasting
confidence: 74%
“…Likewise, OsPSKR12 and OsPSKR15 were also upregulated in response to abiotic stress as depicted in expression analysis done by RNA-seq and real time data. The strong correlation between OsPSKR12 and Exo70 (Fig 7) further supports the role of PSK-PSKR signalling in abiotic stress response as Exo70 is involved in stress tolerance besides its involvement in pollen maturation, germination and pollen tube growth and [54][55][56]. Moreover, the co-expression analysis of PSKR gene, as in Fig 7, showed that their expression is highly correlated to genes encoding for WRKY, MADS-box, NB-ARC, etc.…”
Section: Plos Onesupporting
confidence: 53%
“…Other co-expressing genes include Exo70, WRKY, MADS-box and ABC transporters. Exo70, a component of the exocyst complex, is involved in vesicle trafficking like exocytosis and play crucial role in plant immunity and pollen growth and maturation [53][54][55][56]. While WRKY and MADS-box are the most important class of transcription factors involved in abiotic stress response [57][58][59].…”
Section: Co-expression Network Analysismentioning
confidence: 99%
“…5A). This distal–apical signal gradient is consistent with the results reported for Arabidopsis pollen tubes stained with CFW (Marković et al ., 2019). Signal at the tip was absent in some cells and present in others.…”
Section: Resultsmentioning
confidence: 99%